Twenty-year trend in the prevalence of increased cardiometabolic risk, measured by abdominal obesity, among Spanish children and adolescents across body mass index categories - Helmut Schröder; Charlotte Juton; Michael I. Goran; Julia Wärnberg; Maddi Osés; Marcela Gonzalez-Gross; Narcis Gusi; Susana Aznar; Elena Marín-Cascales; Miguel González-Valeiro; Estefanía Herrera-Ramos; Nicolás Terrados; et al. (BMC Medicine)
Abstract Background Identifying children and adolescents with cardiometabolic risk at an early stage is crucial for effective treatment and prevention. From a practical perspective, this could be accomplished by assessing the presence of abdominal obesity, which serves as a surrogate indicator of increased cardiometabolic risk and is easy to measure. However, the assessment of abdominal obesity via waist circumference has not yet become a standard procedure in pediatric healthcare. The present study aimed to analyze the secular trends in increased cardiometabolic risk, as indicated by waist circumference among Spanish children and adolescents. Methods This study included 4861 children and adolescents aged 8 to 16 years from two nationwide representative cross-sectional surveys, the EnKid study and the PASOS study, conducted in 1998–2000 and 2019–2020, respectively. Anthropometric variables were measured in both surveys by trained personnel. Three different waist-to-height (WHtR) cutoffs were used to define abdominal obesity as criteria for cardiometabolic risk. BMI categories were defined according to the IOTF and WHO growth charts. Results Abdominal obesity [waist to height ratio (cm/cm) > 0.49] significantly increased from 40.7 to 56.1% and 93.8 to 97.2% in participants with overweight and obesity, respectively, between 1998–2000 and 2019–2020 (p < 0.05). Logistic regression analysis, adjusted for sex and age, revealed that the odds of being at increased cardiometabolic risk in 2019–2020 was 1.99 (95% CI 1.48–2.67) in participants with overweight in comparison with 1998–2000. The effect size was comparable among the three WHtR criteria for abdominal obesity or the BMI categories according to IOTF and WHO boundaries. Conclusions The prevalence of Spanish children with increased cardiometabolic risk, identified by abdominal obesity, significantly increased among those with overweight during the last two decades. This finding underlines the need of including the measurement of waist circumference as a standard procedure in pediatric practice.